The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1158/0008-5472.can-10-2449
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioned Endothelial Progenitor Cells Reduce Formation of Melanoma Metastases through SPARC-Driven Cell–Cell Interactions and Endocytosis

Abstract: Tumor progression is associated with the release of signaling substances from the primary tumor into the bloodstream. Tumor-derived cytokines are known to promote the mobilization and the recruitment of cells from the bone marrow, including endothelial progenitor cells (EPC). Here, we examined whether such paracrine influence could also influence the capacity of EPC to interfere with circulating metastatic cells. We therefore consecutively injected EPC prestimulated by tumor-conditioned medium (EPC-CM) and luc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Recent studies by Giannoni et al 18 reported that in prostate carcinoma, direct contact between EPCs and mesenchymal tumour cells induces the EphA2/ephrinA1 signalling to elicit a mesenchymal amoeboid transition in tumour cells, allowing them to attain a metastatic advantage. Moreover, EPCs have been shown to promote melanoma metastasis through the secreted protein acidic and rich in cysteine-driven cell-cell interactions and endocytosis 19. In concert with these previous studies, our results indicate that EPCs recruited to the tumour sites may represent a critical component of ‘soil’ to induce phenotypical switch of a non-metastatic tumour towards one with an increased potential for metastasis.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies by Giannoni et al 18 reported that in prostate carcinoma, direct contact between EPCs and mesenchymal tumour cells induces the EphA2/ephrinA1 signalling to elicit a mesenchymal amoeboid transition in tumour cells, allowing them to attain a metastatic advantage. Moreover, EPCs have been shown to promote melanoma metastasis through the secreted protein acidic and rich in cysteine-driven cell-cell interactions and endocytosis 19. In concert with these previous studies, our results indicate that EPCs recruited to the tumour sites may represent a critical component of ‘soil’ to induce phenotypical switch of a non-metastatic tumour towards one with an increased potential for metastasis.…”
Section: Discussionsupporting
confidence: 83%
“…Although endothelial cells in the tumour microenvironment are known to produce high levels of SPARC, we found that endothelial-derived SPARC did not influence melanoma cell transmigration, further supporting the notion that tumour-and host-derived SPARC have different biological activities and that the origin of SPARC participates to the complexity of SPARC in metastasis 44,47 .…”
Section: Discussionsupporting
confidence: 76%
“…Cells were collected and lysed in with DIGE labelling (DLA) lysis buffer (7 M urea, 2 M thiourea, 4% CHAPS and 30 mM Tris, pH 8.5). Protein labelling with Cy dyes and 2D-electrophoresis were carried out as previously described [ 30 32 ]. The 2D-gels were then scanned using a Typhoon FLA 9500 while the images were analysed using the DeCyder software.…”
Section: Methodsmentioning
confidence: 99%